Bulges in left-handed G-quadruplexes. Issue 3 (27th January 2021) - Das, Poulomi; Ngo, Khac Huy; Winnerdy, Fernaldo Richtia; Maity, Arijit; Bakalar, Blaž; Mechulam, Yves; Schmitt, Emmanuelle; Phan, Anh Tuân
Abstract: G-quadruplex (G4) DNA structures with a left-handed backbone progression have unique and conserved structural features. Studies on sequence dependency of the structures revealed the prerequisites and some minimal motifs required for left-handed G4 formation. To extend the boundaries, we explore the adaptability of left-handed G4s towards the existence of bulges. Here we present two X-ray crystal structures and an NMR solution structure of left-handed G4s accommodating one, two and three bulges. Bulges in left-handed G4s show distinct characteristics as compared to those in right-handed G4s. The elucidation of intricate structural details will help in understanding the possible roles and limitations of these unique structures.